http://i59.tinypic.com/vdp8pf.jpg Thanks in advance!

Hello!

(√7 + √2)*(9 - 2√14)/(√7 - √2) = ?

The interesting part is 9-2√14. 14 is 7*2 and 9 is 7+2, so we have

a^2 + b^2 - 2*ab for a = √7 and b = √2, i.e.

(a-b)^2 = (√7 - √2)^2.

Then one (√7 - √2) goes off numerator and denominator and remains only

(√7 + √2)*(√7 - √2) which is (√7)^2 - (√2)^2 = 7 - 2 = 5.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up